2003
DOI: 10.1124/mol.63.6.1322
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancement of Long-Term Potentiation by a Potent Nitric Oxide-Guanylyl Cyclase Activator, 3-(5-Hydroxymethyl-2-furyl)-1-benzyl-indazole

Abstract: Nitric oxide (NO) is known to affect synaptic plasticity in various regions of the brain via the cGMP-cGMP-dependent protein kinase (PKG) pathway. We found that a novel compound 3-(5-hydroxymethyl-2-furyl)-1-benzyl-indazole (YC-1), a drug known to modulate the response of soluble guanylyl cyclase to NO, greatly potentiates long-term potentiation (LTP). This compound markedly enhanced the induction of LTP in rat hippocampal and amygdala slices by weak tetanic stimulation. The potentiation of LTP by YC-1 was gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 38 publications
(41 reference statements)
4
55
1
1
Order By: Relevance
“…NO/cGMP and PKG contribute to CREB phosphorylation, mediated by the ERK cascade, and also possibly in part via the CaMK pathway (Lu et al, 1999). Interestingly, experiments with YC-1, an agent that augments sGC activation, produced an enhancement of LTP in rat hippocampus and amygdala via an NO/cGMP/PKG/ERK pathway culminating in CREB phosphorylation (Chien et al, 2003). In in vitro brain slice experiments, we found that GT1061 increased the levels of pERK in the CA1 region of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…NO/cGMP and PKG contribute to CREB phosphorylation, mediated by the ERK cascade, and also possibly in part via the CaMK pathway (Lu et al, 1999). Interestingly, experiments with YC-1, an agent that augments sGC activation, produced an enhancement of LTP in rat hippocampus and amygdala via an NO/cGMP/PKG/ERK pathway culminating in CREB phosphorylation (Chien et al, 2003). In in vitro brain slice experiments, we found that GT1061 increased the levels of pERK in the CA1 region of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that NO generated postsynaptically by Ca 2ϩ -calmodulin-dependent NO synthase may act as a retrograde messenger and bind to presynaptic guanylate cyclase to produce cGMP-dependent downstream effects, which strengthen the synaptic connection between coordinately firing cells Son et al, 1998). At the level of systems physiology, one critical function of guanylate cyclase is the facilitation of long-term potentiation in the amygdala (Chien et al, 2003). In rat amygdala slice recordings, stimulation of guanylate cyclase by YC-1 leads to enhanced and enduring potentiation of the corticoamygdala pathway, and this potentiation could be eliminated by concomitant inhibition of NO synthase by L-NAME (Chien et al, 2003).…”
mentioning
confidence: 99%
“…At the level of systems physiology, one critical function of guanylate cyclase is the facilitation of long-term potentiation in the amygdala (Chien et al, 2003). In rat amygdala slice recordings, stimulation of guanylate cyclase by YC-1 leads to enhanced and enduring potentiation of the corticoamygdala pathway, and this potentiation could be eliminated by concomitant inhibition of NO synthase by L-NAME (Chien et al, 2003). Other studies have shown in vivo that inhibition of NO synthase impairs memory in rats as assessed by the Morris water maze (Holscher et al, 1996), and recently, Chien et al (2005) have tested YC-1 in vivo and found improvements in Morris water maze performance.…”
mentioning
confidence: 99%
“…NO/cGMP and PKG contribute to CREB phosphorylation, in part mediated by the ERK cascade, but NO via cGMP-dependent or independent mechanisms may also mediate CREB phosphorylation via PKC and the CaMK cascades [13,43,64]. Interestingly, experiments with YC-1 an agent that augments sGC activation, produced an enhancement of LTP in rat hippocampus and amygdala via an NO/cGMP/PKG/ERK pathway culminating in CREB phosphorylation [42].…”
Section: No Mapk Signaling and Creb Activationmentioning
confidence: 99%
“…Furthermore, the close temporal relationship between activation of the NO/sGC/cGMP signal transduction cascade and improvements in learning and memory suggest a mechanistic link between the two phenomena [40]. Activation of sGC leading to cGMP accumulation will activate PKG that in turn initiates protein phosphorylation cascades leading to activation of transcription regulating factors such as cAMP response element binding protein (CREB), a critical event in both LTP and the establishment of long-term memory [13,42,43].…”
Section: No In Learning and Memorymentioning
confidence: 99%